Causes of Sexual Crimes in Afghanistan and Ways to Prevent Them - Safi, Shahidullah; Shenwari, Zahidullah; Weqar, Matiullah (Integrated Journal for Research in Arts and Humanities, 2024)
Sexual crimes significantly undermine the cultural and moral fabric of society. Similar to other types of crime, these offenses have identifiable causes that must be understood to effectively prevent their occurrence. Recognizing the importance of addressing the root causes of sexual crimes in Afghanistan is crucial for fostering social development, stability, and intellectual and cultural security. This article aims to identify the underlying causes of sexual crimes in Afghan society and propose measures for their prevention, which have contributed to the rise of such offenses. To conduct this research, both library resources and internet sources were utilized. The investigation revealed three primary categories of causes for sexual crimes in Afghanistan: family-related factors, personal issues, and broader social influences. Addressing these factors is essential for formulating effective prevention strategies.